Pseudomemórias: entre a força infomemorial de Mnemosyne e as águas do Lethe no período pandêmico da Covid-19 - Oliveira, Tassyara Onofre de (2022)
The information can determine the continuity or discontinuity of the activities of an organization, a State or a people. In the network society, the power of science has been put to the test by fake news and, while the virus circulates in the physical world, other threats in the virtual world practice misinformation. The objective of this research was to analyze how fake news interfere in the cyclic movement of construction of individual and collective memory and in the emergence of pseudomemories. For this, we seek to present an approach on fake news, its historicity and the main uses in the context of the network society; characterize the relationship between them and individual and collective memories; investigate how they facilitate the cycle of disinformation and the construction of pseudo-memories; to analyze the disinformation strategies practiced during the covid-19 pandemic and how they have the potential to interfere in the field of memory. In the methodological path, we adopted documental research throughout the writing, from the perspective of the taxonomic criteria of the historian Júlio Aróstegui, in the book.“Historical Research” (2006), in combination with the evidentiary paradigm method proposed by Carlo Ginzburg (1990). Finally, we analyze concrete cases that occurred in the period from 2020 to 2022, during the covid-19 pandemic, with the purpose of understanding how fake news becomes pseudo-memories.